4-D Authentication System Using Mouse Gesture - Nikam, Nilima; Mane, Karishma; Kalkute, Minal; Sankhe, Ankita; Mondkar, Leena (Journal of Advance Research in Computer Science & Engineering (ISSN 2456-3552), 2015)
Computer technology is reaching new milestones with every passing day but authentication schemes are still weak in their approach. Many cases of forgeries, hacked accounts are coming up every day. Many authentication schemes have been proposed but each has some drawbacks. Hence, the 3D authentication scheme has been introduced. The 3D password is a multi-layer, multifactor authentication mechanism. It consists of a 3D virtual environment on which a user has to perform certain actions. The sequence of user interactions determines the user’s 3D password. It combines all existing authentication schemes like textual, graphical and bio-metrics into a single 3D virtual environment. This report presents a study of the 3D password and an approach to strengthen it by way of adding a Fourth dimension (4D), that deals with gesture recognition and time recording, and that would help strengthen the authentication paradigm altogether. Hence we attempt to propose a 4D password as a super class of 3D password.